ENHANCEMENT OF THE ANTIOXIDANT CAPACITY OF STRAWBERRIES (Fragaria ananassa Duch.) BY INCORPORATION OF VITAMIN E USING THE VACUUM IMPREGNATION TECHNIQUE - RESTREPO D., Ana María; CORTÉS R., Misael; ROJANO, Benjamín A. (Vitae, 2010)
This study evaluated the antioxidant capacity and vitamin “E” content in strawberries fortified with synthetic vitamin E (dl-α-tocopherol acetate) by vacuum impregnation technique. The vitamin is quantified by HPLC and their levels are recorded per 100 g fresh fruit. The antioxidant capacity was determined during storage in samples packaged with and without vacuum, by the methods DPPH, FRAP and Folin-Cicalteau. The impregnation process can achieve levels in strawberry of 19.12 ± 3.01 mg of vitamin E dl-α-tocopherol acetate/100 g in fresh fruit, with no significant effect over time of storage or the type of packaging. These results were consistent to increased antioxidant capacity as values DPPH, FRAP and Folin-Cicalteau in the order of 14.7%, 82.2% and 56.8% respectively. In general, the results reflect a strengthening of the antioxidant capacity of strawberries, by the effect of vitamin E incorporated by the vacuum impregnation process.